Direct immunofluorescence tests with counterstains for detection of Chlamydia psittaci in infected avian tissues. - Tessler, J (1979)
Different methods of preparation and serological evaluation of rabbit globulins for use in fluorescent antibody conjugate and different methods of counterstaining with fluorescent antibody tests were evaluated for detection of Chlamydia psittaci in infected turkey tissues. The agar gel precipitin reaction was that chosen for testing and selecting antiserums to be used for fluorescein isothiocyanate conjugation. The fluorescent antibody staining was most pronounced with conjugate made from globulins precipitated with ammonium sulfate. A direct fluorescent antibody method with Evans blue counterstain correctly identified "coded" specimens of C. psittaci-infected and noninfected turkey air sacs. However, naphthalene black was superior to Evans blue as a counterstain when infected pericardial sacs were tested.